2000
DOI: 10.1002/1096-9861(20010205)430:2<235::aid-cne1028>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of ocular dominance columns in cat visual cortex by 2 weeks of age

Abstract: Previous anatomic studies of the geniculocortical projection showed that ocular dominance columns emerge by 3 weeks of age in cat visual cortex, but recent optical imaging experiments have revealed a pattern of physiologic eye dominance by the end of the second week of life. We used two methods to search for an anatomic correlate of this early functional ocular dominance pattern. First, retrograde labeling of lateral geniculate nucleus (LGN) inputs to areas of cortex preferentially activated by one eye showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 40 publications
9
77
0
Order By: Relevance
“…Moreover, radioactive tracers have a high potential for spillover in young tissues (LeVay et al, 1978), and, for this reason, the main conclusions of a number of early studies on ocular dominance column (ODC) development (LeVay et al, 1978;Shatz and Stryker, 1978;Stryker and Harris, 1986;Ruthazer et al, 1999) have recently been revised. Modern labeling techniques revealed that segregated ODCs are present at stages of development when radioactive tracers previously indicated they still overlapped (Crowley and Katz, 2000;Crair et al, 2001). Here we used sensitive tracers that do not have the potential for spillover to label retinogeniculate projections arising from both eyes.…”
Section: Early and Rapid Eye-specific Segregation In The Dlgnmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, radioactive tracers have a high potential for spillover in young tissues (LeVay et al, 1978), and, for this reason, the main conclusions of a number of early studies on ocular dominance column (ODC) development (LeVay et al, 1978;Shatz and Stryker, 1978;Stryker and Harris, 1986;Ruthazer et al, 1999) have recently been revised. Modern labeling techniques revealed that segregated ODCs are present at stages of development when radioactive tracers previously indicated they still overlapped (Crowley and Katz, 2000;Crair et al, 2001). Here we used sensitive tracers that do not have the potential for spillover to label retinogeniculate projections arising from both eyes.…”
Section: Early and Rapid Eye-specific Segregation In The Dlgnmentioning
confidence: 99%
“…Furthermore, much is known about the major developmental events in the embryonic macaque visual system, including the timing of retinal ganglion cell and dLGN cell birth and matura-tion (Rakic, 1977a;Shatz and Rakic, 1981;La Vail et al, 1991), the attrition of optic nerve axons (Rakic and Riley, 1983), the ingrowth and elaboration of retinogeniculate axons (Meissirel et al, 1997;Snider et al, 1999), and synapse formation in the dLGN (Hendrickson and Rakic, 1977). Because Rakic's study relied on tracers now known to be prone to "spillover" (LeVay et al, 1978;Ruthazer et al, 1999;Crair et al, 2001) and long postinjection survival periods, a precise delineation of when eye segregation occurs in this important model species is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…ODCs form long before there is sensory input and very soon after LGN neurons arrive at layer 4 of visual cortex (Horton and Hocking, 1996;Crowley and Katz, 2000;Crair et al, 2001). As a means of determining whether retinal activity is required for the early formation of ODCs, Crowley and Katz recently conducted binocular enucleations very early in development (Crowley and Katz, 1999).…”
Section: Do Retinal Waves Play a Role In The Development Of Cortical mentioning
confidence: 99%
“…In that study, NGF was delivered from P28 to P42. Since ocular dominance columns are detectable in the cat by the second postnatal week, both anatomically (Crair et al, 2001) and functionally (Crair et al, 1998), the Cabelli et al study examined whether NGF had any e¡ect on the later stages of ocular dominance column formation. To determine if NGF has a role in the initial segregation of geniculocortical a¡erents into ocular dominance columns, we infused NGF for 4 weeks at a concentration of 0.2 mg/ml locally into primary visual cortex of one hemisphere beginning at P14^P18.…”
Section: Local Cortical Infusion Of Ngf Has No E¡ect On Ocular Dominamentioning
confidence: 99%